Metric culture : ontologies of self-tracking practices - Ajana, Btihaj (Emerald Publishing Limited, 2018)
We live in a "metric culture" where data, algorithms, and numbers play an unmistakably powerful role in defining, shaping and ruling the world we inhabit. Increasingly, governments across the globe are turning towards metric technologies to find solutions for managing various social domains such as healthcare and education. While private corporations are becoming more and more interested in the collection and analysis of data and metrics for profit generation and service optimisation. What is striking about this metric culture is that not only are governments and private companies the only actors interested in using metrics and data to control and manage individuals and populations, but individuals themselves are now choosing to voluntarily quantify themselves and their lives more than ever before, happily sharing the resulting data with others and actively turning themselves into projects of (self-) governance and surveillance.'Metric Culture' is also not only about data and numbers alone but links to issues of power and control, to questions of value and agency, and to expressions of self and identity. This book provides a critical investigation into these issues examining what is driving the agenda of metric culture and how it is manifested in the different spheres of everyday life through self-tracking practices. Authors engage with a broad range of topics, examples, geographical contexts, and sites of analysis in order to account for the diversity and hybridity of metric culture and explore its various social, political and ethical implications.
Includes index.
Keywords: Technology -- Social aspects.; Metrology.; Metric projections.; Social Science -- Disease & Health Issues.; Medical sociology.; elektronické knihy; electronic books